Reactive Oxygen and Nitrogen Species in the Development of Pulmonary Hypertension - David J.R. Fulton; Xueyi Li; Zsuzsanna Bordan; Stephen Haigh; Austin Bentley; Feng Chen; Scott A. Barman (MDPI AG, 2017)
Pulmonary arterial hypertension (PAH) is a progressive disease of the lung vasculature that involves the loss of endothelial function together with inappropriate smooth muscle cell growth, inflammation, and fibrosis. These changes underlie a progressive remodeling of blood vessels that alters flow and increases pulmonary blood pressure. Elevated pressures in the pulmonary artery imparts a chronic stress on the right ventricle which undergoes compensatory hypertrophy but eventually fails. How PAH develops remains incompletely understood and evidence for the altered production of reactive oxygen and nitrogen species (ROS, RNS respectively) in the pulmonary circulation has been well documented. There are many different types of ROS and RNS, multiple sources, and collective actions and interactions. This review summarizes past and current knowledge of the sources of ROS and RNS and how they may contribute to the loss of endothelial function and changes in smooth muscle proliferation in the pulmonary circulation.